Optical and electronic properties of hybrid organic-inorganic perovskite type [NH3-(CH2)3-COOH]2HgCl4 - Ouaaka El Mustafa; Khechoubi El Mostafa (E3S Web of Conferences)
The hybrid organic-inorganic perovskite type [NH3-(CH2)3-COOH]2HgCl4 was synthesized at room temperature using the slow evaporation method. X-ray Diffraction powder (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), and UV-visible spectroscopy were used to characterize the phase purity, the functional groups, and the optical properties, respectively. [NH3-(CH2)3-COOH]2HgCl4 crystallizes in C2/c space group with cell parameters a=29.2762 (2) Å, b=11.0408 (1) Å, c=11.3944 (1) Å, β=112.532 (2) Å and Z=8.The atomic arrangement shows an alternation of organic and inorganic entities. The cohesion of the bulk crystal is realized via N-H.…Cl and O-H…O hydrogen bonding. The reflectance (R %) was recorded and applied to deduce the optical band gap. The optical results show that this hybrid material undergoes a direct optical transition and presents an energy gap value of about 2.75 eV. The electronic properties total and partial densities of states (TDOS, PDOS), and band structure are calculated using density functional theory (DFT). The experimental and theoretical (DFT) band gap values are compared.